PknB and STP as potential targets of luteolin in combating Trueperella pyogenes infections - Yueting Guo; Hongyu Su; Lihui Yu; Yingyu Wang; Chunlian Tian; Dexian Zhang; Yuru Guo; Mingchun Liu (Scientific Reports)
Abstract Trueperella pyogenes (T. pyogenes) is a significant opportunistic pathogen that causes suppurative infection in many animals, as well as humans. Considering the strong drug resistance of T. pyogenes, the development of novel antibacterial drugs and drug targets to combat infections is necessary. Serine/threonine protein kinases (STKs) and serine/threonine phosphatases (STPs) play pivotal roles in the physiological processes, pathogenesis, and resistance of several important bacterial pathogens, indicating their potential as antimicrobial drug targets. In this study, we aimed to investigate the effects of luteolin, a natural flavonoid, on serine/threonine protein kinase B (PknB) and serine/threonine phosphatase (STP). The results revealed that after T. pyogenes was treated with 1/2 MIC (39 μg/mL) luteolin for 36 h, the transcription and translation levels of the pknB and stp genes decreased significantly. Molecular docking revealed that hydrophobic forces were predominant in the interaction between luteolin and PknB, whereas hydrogen bonding was predominant in the interaction between luteolin and STP. The results of the molecular interaction assay revealed that the KD value of luteolin with PknB and STP were 3.125 × 10–4 M and 1.128 × 10–5 M, respectively. Additionally, luteolin could inhibit the activities of PknB and STP. Our study demonstrated that luteolin can inhibit PknB and STP at multiple levels, and it is expected to be used as a PknB/STP inhibitor to develop new drugs against drug-resistant bacterial infections.